(untitled) (Conferencea, 2023)
The advantage of being alone in Hawthorne’s work Hawthorne’s work is defined by his autobiography. The Puritan religion entered his consciousness from childhood. Already in his teens, he was imbued with the spirit of New England, in which his pedantic and strict ancestors lived and trained. The habit of being alone did not bring him tragedy, on the contrary, it contributed to his spiritual growth. The habit added advantage in terms of creative growth. He was imbued with determinism. His novels and novels clearly have a spiritual feeling. You can feel the verbs reflecting his bio-life, his most famous novel, such as: "Scarlet Asomovruli" story "Roger Malvin’s Funeral" and others. The plot of the work and the spiritual crisis that develops in it clearly show the writer’s attitude and spiritual mood in relation to the dilemma faced by the hero. Although Hawthorne is referred to as a romantic writer, he is a writer with a very distinctive handwriting. , is interested in moral romance. He explores the spiritual labyrinths of man. His creation is a combination of thought and art